Integration of Solar Power in Hydroponics as Community Empowerment in Meruya Selatan - Andika, Julpri; Suwoyo, Heru; Dirman, Angela; Putra, Firoos Safana; Jibran, Alwan (Universitas Mercu Buana, 2025)
The condition of the area in Gang Hijau Swakarya, South Meruya, is that there is still land around residential areas that have not been utilized for greening and also has open land that is very rich in receiving sunlight. However, people have not been able to utilize sunlight as a renewable energy source for electrical energy conversion. If utilized, this can reduce the cost of expenses so that the selling price of the product can be maximized. Therefore, this community service activity is carried out with the aim of increasing food security through developing an efficient and environmentally friendly hydroponic farming system in an urban environment by utilizing renewable energy and introducing and implementing solar cell technology and nutrient control to provide alternative energy sources and optimize agricultural yields. By providing proper nutrition to plants. To achieve these goals, methods and stages such as the implementation of socialization, training, technology application, evaluation and mentoring, and program sustainability are implemented. As a result, Participants from the community expressed a high level of satisfaction with the training methods and technology implementation provided with the average of the standard deviation value was 0.020, close to 0.